Introduction to missiology - Tippett, Alan R. (William Carey Library, 1987)
While teaching at Fuller School of World Mission, Alan Tippett inspired and challenged the founding generation of "great commission" (or "church growth") missiologists. This collection brings together almost 40 of his best writings. In a style that is both academic and personal he deals first with missiological theory, then with anthropological and historical dimensions of missiology. He then treats a number of specific missiological problems from these perspectives, including seminal material on power encounter.